Evolução da desigualdade de renda no Ceará: 1995-2007 - Pontes, Davi Oliveira (2009)
The State of Ceará has been marked by regional disparities in recent years where modern and dynamic regions contrast to backward ones. In this scenario, this paper aims to test for the convergence of the per capita income among municipalities as well as the sustainability of the U-inverted Kuznets’ curve, followed by the determinants of the income inequalities based upon decomposition of Theil index in five factors: education, gender, race, age, urban areas. Due to data availability, the first two objectives were attained for the ninety decade. Despite testifying convergence, the econometric predictions for the last year of the series indicate that municipalities are still located in the upward portion of Kuznets’ curve. As inequality is concerned, education has been proved to be the leading factor for its explanation. On average in the period 1995-2007, it accounts for 28% of the state inequality, as the index is measured between groups, while any other factor represents no more than 4,5%. Along that period, the inequality index takes a inverted-U shape, and only the participation of the urban area factor in the index follows the same shape. Finally, It is quite worth noting that after adding the last factor to explain inequality, 40% of it is yet to be explained. This factor calls for further investigations.